Should an ESP Course be Specific or General? A Literature Review of the Specificity Debate - Nhã, Vũ Thị Thanh (VNU Journal of Foreign Studies; Vol 31 No 4, 2015)
Subject content is an important part of ESP courses. However, it is controversial how much subject content should be integrated into course content. This paper reviews the debate over specificity of ESP courses in three ESP development periods since 1960s. It will provide ESP practitioners, course writers and managers a theoretical overview to inform their teaching and researching practices. Keywords: Specificity, ESP, literature review, course development.